The democratic role of social media in political debates: The use of Twitter in the first televised US presidential debate of 2016. Issue 2 (3rd April 2019) - Robertson, Craig T.; Dutton, William H.; Ackland, Robert; Peng, Tai-Quan
ABSTRACT: Live social media commentary increasingly accompanies televised political debates. This study examines the democratic role of live Twitter commentary by analyzing a sample of tweets published during the first 2016 presidential debate between Trump and Clinton. The practices of live commenters – including joke-sharing and fact-checking – are assessed in light of six perspectives on the democratic utility of such commentary. Results show that while Twitter commentary was predominantly humorous and driven by negativity towards the candidates, a sizeable proportion of users actively engaged in practices of alternative interpretation, critique, and correction, seeking democratic accountability.